American depositary receipts (adr) holdings of U.S. based emerging market funds - Aggarwal, Reena 1985- (Policy research working paper, 2005)
"For a foreign "issuer," the benefits of cross-listing in the United States are extensively documented in the literature. However it is not clear what motivates "investors" to hold American Depositary Receipts (ADRs) rather than the underlying stock of these issuers. The authors address the investors' choice to purchase local shares versus investing in ADRs. Specifically, they analyze the investment allocation decision of mutual fund managers to invest in emerging market firms that are listed in their domestic markets and have also issued ADRs in the United States. Although legal provisions (governance/investor protection) are typically assumed to affect ADRs and their underlying domestic shares equally, investors holding ADRs may have a higher level of legal protection as these securities are issued and traded in the United States. The authors' results are consistent with this "better legal protection" hypothesis as they find that funds prefer to hold ADRs rather than the underlying shares if the issuer is from a country with weak investor protection laws. Also, theoretical models of multiple trading exchanges predict that trading should tend to aggregate in the market with the lowest transaction costs. Similarly, the relative liquidity of an ADR compared to that of its underlying stock should also affect the funds' relative holding of the ADR versus the underlying stock. Consistent with this "ease of transaction" hypothesis the authors find that if an issuer is based in a country with a relatively small stock market, low level of trading volume, and high transaction costs, funds tend to hold a larger proportion of their investments in the ADR. Furthermore, funds hold a larger fraction of their investment in the ADR if the ADR trading volume is high relative to its domestic security trading volume.